2006
DOI: 10.1145/1215942.1215943
|View full text |Cite
|
Sign up to set email alerts
|

Motivations of contributors to Wikipedia

Abstract: This paper aims to explain why people are motivated to contribute to the Wikipedia project. A comprehensive analysis of the motivations of Wikipedians is conducted using the iterative methodology developed by Batya Friedman and Peter Kahn in Value Sensitive Design and Information Systems and co-developed by Nissenbaum and Friedman in Bias in Computer Systems . The Value Sensitive Design (VSD) approach consists of three stages: Empirical Investigation, Conceptual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
96
0
9

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(107 citation statements)
references
References 2 publications
2
96
0
9
Order By: Relevance
“…Nov (2007) found that the top three motivations of Wikipedians were: 9 fun (enjoying oneself), ideology ("information should be free") and values (helping others, sharing knowledge). As already observed by Kuznetsov (2006) there is a significant overlap between…”
Section: Wikipedians' Values As a Factor In The January 18 Protests: supporting
confidence: 54%
“…Nov (2007) found that the top three motivations of Wikipedians were: 9 fun (enjoying oneself), ideology ("information should be free") and values (helping others, sharing knowledge). As already observed by Kuznetsov (2006) there is a significant overlap between…”
Section: Wikipedians' Values As a Factor In The January 18 Protests: supporting
confidence: 54%
“…[9] People who use Wikipedia very often as readers will start to correct errors and eventually become authors. [10] A lot of time has been spent on measuring the quality of Wikipedia articles in a quantitative manner. In the meantime, Wikipedia articles are increasingly being used as references in other contexts.…”
Section: Results Of Library Researchmentioning
confidence: 99%
“…Here we see that editors and authors tend to come and go very quickly [4,12] and, as articles mature, it might be more valuable to have a larger set of contributors or maintainers [11]. Yet Wikipedia differs in that the act of maintenance is really about just that-maintenance.…”
Section: Discussionmentioning
confidence: 98%